Justice in the Digital State - Tomlinson, Joe (Policy Press, 2019)
Exploring how justice is delivered at a time of rapid technological transformation, Justice in the Digital State exposes urgent issues surrounding the modernisation of courts and tribunals whilst examining the effects of technology on established systems. Case studies investigate the rise of crowdfunded judicial reviews, the digitalisation of tribunals and the rise of 'agile' methodologies in building administrative justice systems. Joe Tomlinson's cutting-edge research offers an authoritative and much-needed guide for navigating through the challenges of digital disruption.